Técnica para a redução do tempo de ensaios de termografia ativa modulada em células fotovoltaicas - Silva, Renan Oliveira (2024)
Lock-in Thermography is a technique used in non-destructive testing to characterize defects in various materials, including electronic components and photovoltaic cells. In this type of thermography, tests are performed using a periodic signal that heats the photovoltaic cells for a long period of time, since the analysis is performed when the material reaches a steady state temperature. This work proposes a method to reduce test time, based on the thermal transient of temperature generated during heating to estimate the thermal information of the material in steady state. Thus, after data processing, it is possible to obtain images that represent the internal behavior of the material similar to those obtained using the classical method. In developing the method, analyses of the behavior of the cells during the thermal transient of the tests were performed, comparing the images generated during these periods of time with the reference image obtained in steady state, using similarity metrics. In addition, test parameters and preprocessing techniques were varied in search of a better understanding of the phenomenon. The use of the proposed method allowed obtaining images that represent the characteristics of the cells studied, as well as similar to those obtained using the classical method, reducing the test time by approximately 80%.